Molecular characterization of putative parasitism genes in the plant-parasitic nematode Meloidogyne hispanica. Issue 1 (16th October 2014) - Duarte, A.; Maleita, C.; Tiago, I.; Curtis, R.; Abrantes, I.
Abstract: Meloidogyne hispanica ( Mhi ) is a difficult-to-control polyphagous root-knot nematode (RKN) species of emerging importance for economically valuable crops. Nematode secretions are likely to be the first signals perceived by the plant and are thought to be involved in various aspects of the plant–nematode interaction. The aims of this work were to identify and characterize M. hispanica parasitism genes: cathepsin L cysteine protease ( cpl-1 ), calreticulin ( crt-1 ), β-1, 4-endoglucanase-1 ( eng-1 ) and manganese superoxide dismutase ( mnsod ). As there are no genomic data available for M. hispanica, primers were designed from the conserved regions of the putative parasitism genes in M. incognita and M. hapla and used to amplify the genes in M. hispanica, which led to the successful amplification of these genes in M. hispanica. Partial gene sequences were also obtained for M. arenaria, M. hapla, M. hispanica, M. incognita and M. javanica cpl-1, crt-1, eng-1 and mnsod genes, and their phylogenetic relationship analysed. In order to determine whether these genes are differentially expressed during M. hispanica development, cDNA was amplified from mRNA isolated from eggs, second-stage juveniles (J2) and females. Amplification products were observed from cDNA of all developmental stages for the Mhi-cpl-1 and Mhi-crt-1 genes. However, the gene Mhi-crt-1 exhibited intense amplification bands in females, while the Mhi-eng-1 gene was equally amplified in eggs and J2 and the Mhi-mnsod gene was only expressed in eggs. In comparison to the other RKN species, the genes Mhi-eng-1 and Mhi-mnsod showed transcription in different nematode developmental stages.